History of screening by BreastScreen New South Wales of women with invasive breast cancer. (February 2020) - Li, Ming; Warner-Smith, Matthew; McGill, Sarah; Roder, David; Currow, David
Highlights: Breast screening is directed at finding breast cancers earlier. For women diagnosed with breast cancer at age 50–69 years. 73 % had a history of screening. 60 % have been screened in the 24 months before diagnosis. Screening coverage in the 24 months before diagnosis did not vary by socioeconomic status of residential area. A history of breast screening is less frequent in Indigenous than non-Indigenous women with breast cancer. Abstract: Background: The principal target age for Australian BreastScreen services was 50–69 years in 1991–2013 and 50–74 years from 2014. History of BreastScreen NSW screening participation of NSW women diagnosed with breast cancer in 2005–2014 was examined using linked BreastScreen and Cancer Registry data. Methods: Differences in BreastScreen participation were investigated by sociodemographic and tumour characteristics, and diagnostic period, using the Pearson Chi-square test, or Fisher's Exact test when numbers were small, and by multivariate logistic regression. Results: At breast cancer diagnosis, a history of BreastScreen participation varied by age from 23 % for 40−49 years to 68 % for 50–59 years, 72 % for 70–74 years and 78 % for 60–69 years. Among women experiencing breast cancer at age 50–69 years, 60 % had participated in BreastScreen <24 months of diagnosis. Higher odds of BreastScreen participation applied to residents of inner regional and remote compared with major city areas and for women with localized compared with more distant cancer spread. BreastScreen participation was lower in Indigenous than non-Indigenous women. Differences in participation existed by country of birth and residential location, but they were not pronounced. Conclusion: The history of BreastScreen NSW participation of 60 % <24 months for women aged 50–69 years at breast-cancer diagnosis is less than the 70 % target for biennial screening coverage at a population level, but this target has never been reached by an Australian jurisdiction. Qualitative research of screening barriers and opportunities may provide a useful guide for reducing barriers across the population.